After the project is over: Measuring longer-term impacts of a food safety intervention in Senegal. (May 2021) - Leavens, Laura; Bauchet, Jonathan; Ricker-Gilbert, Jacob
Highlights: Estimated the two-year longer-term impacts of an aflatoxins-reducing RCT in Senegal. In the longer term, only providing training, a hygrometer, and a tarp had a statistically significant impact on aflatoxins. Estimates of the marginal effects of each technology indicated that the tarp was the key input driving these results. In the longer term, hermetic bags did not have a statistically significant effect, likely due to supply chain issues. Results suggest providing training and a tarp is "moderately cost-effective, " based on WHO guidelines. Abstract: Few studies in the economics of food safety literature follow-up with participants in the years after an intervention. This limits our ability to assess an intervention's longer-term benefits, sustainability, and cost-effectiveness. In this article we follow up with about 2000 smallholder farming households in Senegal two years after they participated in a randomized controlled trial aimed at reducing levels of aflatoxins in stored maize. In the longer-term, providing a combination of training, a moisture meter, and a tarp decreased levels of aflatoxins by about 20 percent compared to the control group. Estimates of the marginal effect of each input in the bundle indicated that the tarp was the key input driving these results. Additionally, we found that providing training and a tarp was moderately cost-effective based on WHO guidelines for public health interventions. Hermetic (airtight) maize storage bags, which were found to be the most effective technology at reducing aflatoxins immediately after the intervention in 2017, did not statistically significantly lower aflatoxins levels in 2019. This is likely due to supply chain issues in which respondents had difficulties in purchasing replacement bags from local suppliers. Differences between the short-term and longer-term findings underscore the need for longer follow-up periods after conducting an intervention.